Efektivitas Penggunaan Strategi Pembelajaran Dalam Meningkatkan Hasil Belajar Siswa Di SD Negeri 060822 Medan - Annisa Rahmadani; Fitri Khoiroh Sayidah Harahap; Nabila Ulkaira; Yunita Azhari; Safran Hasibuan (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Learning strategies are one of the important components for teachers to prepare in the teaching and learning process. This research aims to describe the effectiveness of using learning strategies in improving student learning outcomes at SD Negeri 060822 Medan. This type of research is descriptive qualitative research, namely research in the form of narrative data or utterances from people being observed (orally). The data sources for this research use observation and interviews. The results of this research indicate that the teacher's role in designing and implementing learning strategies greatly influences the effectiveness of learning. Teachers who are effective in understanding student needs and developing appropriate strategies can create a dynamic and supportive learning environment. In addition, the use of appropriate learning strategies can have a positive impact on student learning outcomes, increase understanding of concepts, and stimulate student involvement in learning.